ANALYSIS OF E-MARKETING, SOCIAL MEDIA MARKETING, AND E-WOM ON CONSUMER PURCHASE DECISIONS - Eliza, Eliza -; Leni, Puspa; Mulya, Jumiatul; Megawati, Megawati (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2023)
The purpose of this study is to examine the effect of E-marketing and social media marketing toward consumer purchase decisions during the post Covid-19 pandemic with E-WOM as the mediating variable. The sample in this study were 238 respondents who shopped online at Ecommerce during the post Covid-19 pandemic. The sampling technique used of the reserach was non probability sampling through purposive sampling technique. Technique of data analysis was using SmartPLS. The results of the study show that the direct effect of social media marketing on purchase decisions is not significant, the direct effect of social media marketing on E-WOM is positive and significant. The direct effect of E-marketing on purchase decisions has a positive and significant effect, the direct effect of E-marketing on E-WOM has a positive and significant effect. The direct effect of E-WOM on purchase decisions is positive and significant. The effect of social media marketing and E-marketing through E-WOM is not significant for consumer purchase decisions during the post Covid-19 pandemic. It can be said that the consumer purchasing decisions during the post Covid-19 pandemic are influenced by E-marketing, social media marketing, and E-WOM.